Nárek – izgubljen slovenski folklorni žanr - Zemljak Jontes, Melita (Slavia Centralis, 2020)
The Lament – a lost Slovenian folk genreLaments and lamentation began to dwindle in the mid 19th century. Fortunately, they have been documented in the form of recorded texts and descriptions of the custom. The texts reveal surprising poetic intensity, driven by powerful experiences and emotions. The preserved ritual texts with ancient mythological features (Bela krajina), with data on their performance (Istria), and with indications of the deterioration of their original function (Resia) are outstanding documents of a past lifestyle (Prekmurje – Porabje). Modern lifestyles and ideas obscured the original meaning and sense of lamentation. Robbed of its spiritual significance, lamentation was for some time preserved as a social corrective (poor women were paid for it). Nowadays, lamentation is replaced by funeral speeches.
Keywords: genre; literary folklore; custom; corpse; lamentation